Higher P-Wave Dispersion in Migraine Patients with Higher Number of Attacks - A. Koçer; M. Eryılmaz; H. Tutkan; N. Ercan; Z. S. Küçükbayrak (The Scientific World Journal)
Objective and Aim. An imbalance of the sympathetic system may explain many of the clinical manifestations of the migraine. We aimed to evaluate P-waves as a reveal of sympathetic system function in migraine patients and healthy controls. Materials and Methods. Thirty-five episodic type of migraine patients (complained of migraine during 5 years or more, BMI < 30 kg/m2) and 30 controls were included in our study. We measured P-wave durations (minimum, maximum, and dispersion) from 12-lead ECG recording during pain-free periods. ECGs were transferred to a personal computer via a scanner and then used for magnification of x400 by Adobe Photoshop software. Results. P-wave durations were found to be similar between migraine patients and controls. Although P WD (P-wave dispersion) was similar, the mean value was higher in migraine subjects. P WD was positively correlated with P max (P<0.01). Attacks number per month and male gender were the factors related to the P WD (P<0.01). Conclusions. Many previous studies suggested that increased sympathetic activity may cause an increase in P WD. We found that P WD of migraine patients was higher than controls, and P WD was related to attacks number per month and male gender. Further studies are needed to explain the chronic effects of migraine.